O processo de escolha das coleções de letramento e alfabetização linguística do Programa Nacional do Livro Didático - Bisognin, Andrea Guida (2010)
The main object of this research is the process of choosing the books of the Programa Nacional do Livro Didático (PNLD) and focuses on the selection of collections from Literacy and Initial Linguistic Literacy by teachers who teach in public schools at Guarulhos-SP to the extensions of Elementary School (Ensino Fundamental EF) during nine years. The research started on the analysis of the quality of teacher s participation regarding the specificity required by the task of choosing the books for First and Second years of this segment of Basic Education should consider the conditions under which the PNLD is held. Accordingly, aspects of the microstructure, such as school organization for the selection of textbooks, are discussed in the relation with the macrostructure the actions of the federal government, the commercial practices of publishers, the municipal level of management on the process, as well as national education policy that determine the enrollment of children in Elementary School from six years old. To describe the practices experienced by the Guarulhos´s teachers during the choice of PNLD 2010 books on this network of relationships were used as sources: interviews with staff involved in the process of choice (teachers, coordinators, principals), reports written during the observations in loco, reports and official documents (federal and municipal) related to the regulations on Elementary School of nine years in the education system, on pedagogical matters and on the execution of PNLD. Authors such as Apple, Choppin and Gimeno Sacristán provide theoretical support for this analysis. This research allowed its author to: verify that the obstacles that hinder the process of selecting books for students enrolled in the 1st and 2nd years of Basic Education are similar to those already identified in previous research; observe that the specificities of this education segment were not taken into account, despite the changes, both in the organization of the municipal school system to incorporate to the Basic Education System children from age six, as well as in the guidelines on the teaching of reading, writing and speaking in those classes; identify aspects in the management of spaces of collective work in schools that have imposed limits on the possibilities of holding discussions on a teaching project for the acquisition of literacy of students in the early years of Basic Education, as well as making effective changes in the process of selecting textbooks, the recognition that the choice of these books from the last edition of the (PNLD) took place in the midst of a transition process, even in a school system in which debates on the registration of children in six years in the Basic Education began nearly ten years ago. And that, therefore, any attempt to analyze the quality of teachers' participation in the selection of book collections for students of 1st and 2nd years requires needs to be contextualized in the web of relationships that this research sought to weave